5x-2=3x*2

Simple and best practice solution for 5x-2=3x*2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-2=3x*2 equation:


Simplifying
5x + -2 = 3x * 2

Reorder the terms:
-2 + 5x = 3x * 2

Reorder the terms for easier multiplication:
-2 + 5x = 3 * 2x

Multiply 3 * 2
-2 + 5x = 6x

Solving
-2 + 5x = 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-2 + 5x + -6x = 6x + -6x

Combine like terms: 5x + -6x = -1x
-2 + -1x = 6x + -6x

Combine like terms: 6x + -6x = 0
-2 + -1x = 0

Add '2' to each side of the equation.
-2 + 2 + -1x = 0 + 2

Combine like terms: -2 + 2 = 0
0 + -1x = 0 + 2
-1x = 0 + 2

Combine like terms: 0 + 2 = 2
-1x = 2

Divide each side by '-1'.
x = -2

Simplifying
x = -2

See similar equations:

| P(x)=4x^2+24x+36 | | 4(3v-1)=5(4v-1)-4(3v-2) | | 1/3/96 | | 3.5w=31.5 | | 2x-8(9-x)=10 | | x-8/6/9=3/5 | | x+3.9=23.2 | | m+15=240 | | X-10-2x=14 | | 4x-(6x-2)=8x-98 | | 3-2y+12y= | | (11x+10)+(7x-10)=180 | | (6-x)/4=-6 | | 0.5f=f-3 | | 1/3x=x-44 | | 3x(2y+7)=3 | | 8x+12-6x+19=-4 | | 4(5-4)+14= | | 1/2(6x-2)= | | 5b/2 | | 4n-14=6 | | -1=2w-11 | | 3t+11=21 | | X^2-0.75=x | | 1/2(4-2x)= | | 1/2÷3/4 | | 3p+3=p+2 | | 11-5+x=5+4-2 | | 43s^2+14s=0 | | 2y=3y-8 | | -3+13=15x-4-14x | | 44+(7x-3)=90 |

Equations solver categories